Overview of PCR. Issue 18 (23rd October 2018) - Kuslich, Christine D.; Chui, Buena; Yamashiro, Carl T.
Abstract: The polymerase chain reaction (PCR) has revolutionized molecular biology and has enabled many other technologies and applications commonly used in research, and is part of many life science products. This unit will cover the basic principles of PCR, including how to carry out PCR in a laboratory that has not used this powerful technique previously. In addition, a number of different applications utilizing the basic PCR technique will be described. © 2018 by John Wiley & Sons, Inc.